2010
DOI: 10.1111/j.1526-4637.2010.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain after Spinal Cord Injury: Results of a Long-Term Study

Abstract: Spinal cord injury-related pain interferes with daily activities of patients and significantly influences their quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 30 publications
(55 reference statements)
8
40
0
Order By: Relevance
“…4,22,23 In addition, SCI characteristics such as age at SCI, duration after SCI and completeness of injury were not related to pain ratings. 8 It has been shown that incomplete spinal injuries were more likely to result in pain than complete injuries, whereas no significant association between the severity of pain and completeness of injury was found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,22,23 In addition, SCI characteristics such as age at SCI, duration after SCI and completeness of injury were not related to pain ratings. 8 It has been shown that incomplete spinal injuries were more likely to result in pain than complete injuries, whereas no significant association between the severity of pain and completeness of injury was found.…”
Section: Discussionmentioning
confidence: 99%
“…3 Although the pain often starts within the initial 6 months of SCI, it frequently persists and sometimes can even become aggravated over time. 4 As pain is known to affect recreational activities and vocational status, 5 quality of sleep 6 and sexuality, 7 it can have a major role in QoL, mood and rehabilitation outcome. For many of them, the pain is severe and accompanied by reduced physical functioning, eventually lowering the QoL.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,4,12 To improve resource allocation and dedicated research within the field, promoting awareness and improved advocacy of NP after SCI was emphasized by the panel.…”
Section: Limited Connections Across the Care Continuummentioning
confidence: 99%
“…Neuropathic pain (NP) is one of the most common complications after spinal cord injury (SCI) [1][2][3][4] and negatively interferes with rehabilitation, function, mood, and quality of life. 3,[5][6][7] Though NP is a significant issue for those with SCI, successful clinical management resulting in reduced pain intensity and improved function can be difficult to achieve and implement, 5,6,8 and evidence for best practices is limited.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Pain negatively interferes with sleep, return to work, health-related quality of life and participation in social activities. 3 In addition, pain is associated with poorer rehabilitation outcomes and directly contributes to disability.…”
Section: Introductionmentioning
confidence: 99%